Penerapan Model Pembelajaran Discovery Learning Untuk Meningkatkan Hasil Belajar Siswa Kelas V Di Sd Muhammadiyah Perumnas Kota Makassar - Muariah Muariah; Sayidiman Sayidiman; Muhammad Irfan (CV. SINAR HOWUHOWU, 2026)
This study was motivated by the low learning outcomes of fifth-grade elementary school students in Natural and Social Sciences (IPAS), which were caused by teacher-centered learning that limited students' active participation during the learning process. This study aimed to describe the implementation of the Discovery Learning model to improve the IPAS learning outcomes of fifth-grade students at SD Muhammadiyah Perumnas Makassar. The research employed a qualitative approach using Classroom Action Research (CAR), which was conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The research subjects were 17 fifth-grade students in the second semester of the 2025/2026 academic year. Data were collected through observation, tests, and documentation and analyzed using qualitative descriptive techniques. The findings revealed that the implementation of the Discovery Learning model improved both the learning process and students' learning outcomes. Teacher and student activities increased from the